The Development of Takraw Ball Media for Sepak Takraw Learning for Sports Education Students - Andi Kasanrawali; Albadi Sinulingga; Endang Pratiwi; Hernawan Hernawan (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2023)
POR Uniska students still need more confidence during takraw practice activities because the ball used (media) is very hard, and the takraw ball is factory-made. This study aims to determine the development of takraw ball learning media to determine its attractiveness level. This type of research is Research and Development (R&D) adapted by Sugiono from his method. The subjects of this research were MAB POR UNISKA students in regular class B 2020, and the data collection instrument used was a questionnaire given to material experts, media experts, and Sepaktakraw course lecturers to test the quality of rubber rattan takraw balls for MAB POR UNISKA students. The development of this takraw ball was carried out and adapted from the research and development (R&D) method, which consists of several stages following the steps of Bord and Gall, including identification of potential and problems, data collection, product design in the form of a simple takraw ball, design validation, design revision, product trial, and final product revision. The results of the assessment of simple takraw balls in sepak takraw learning include: the material expert assessment gives a final average score of 96.3 with very interesting criteria, the media expert gives a final average score of 80.6 with very interesting criteria, and the course instructor gives a score of 90.83 with very good criteria. The product trial results showed an average final score of very good attractiveness. The development of rubber rattan takraw ball learning media for MAB POR UNISKA students is very suitable for use as learning media